El Bélgica de Guerlache en el imaginario social de Punta Arenas, , 1897-1899 - Jara Fernández, Mauricio (Centro de estudios hemisféricos y polares, 2013)
This article analyzes, based on the information in the newspaper El Magallanes of Punta Arenas and other publications, the perception that was created among the population of this southern Chilean city by the Antarctic expedition of between 1897 and 1899 and the activities carried out by the scientists and crew of the Belgique commanded by Lieutenant Adrien de Gerlache. Due to the fact that this expedition was made up of people from various nations and that it was aimed at reaching the South Pole provoked unusual interest and awoke an attractive interest for scientific topics and southern and antarctic policies. El artículo analiza en base a informaciones del periódico El Magallanes de Punta Arenas y otras publicaciones, la percepción que se generó en la población de esta austral ciudad chilena por la expedición a la Antártica entre 1897 y 1899 y las actividades realizadas por los científicos y tripulantes del Bélgica comandado por el teniente Adrien de Gerlache. Por el hecho de ser una expedición integrada por personas de varias naciones y en busca del polo sur, su arribo y permanencia en la rada de Punta Arenas provocó un inusitado interés y despertó una atractiva afición por los temas científicos y políticos australes y antárticos.